2017
DOI: 10.1097/qad.0000000000001496
|View full text |Cite
|
Sign up to set email alerts
|

New-onset diabetes in HIV-treated adults

Abstract: In addition to traditional risk factors, lipodystrophy and use of didanosine were strongly associated with development of incident diabetes. Given the higher rate of cardiovascular-cerebrovascular complications and chronic kidney disease among patients with diabetes mellitus, careful assessment and appropriate management of diabetes mellitus are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…Our study showed that the risk of death in patients diagnosed DM tended to be higher after 4 years of follow-up, a finding similar to that reported by a previous study in Thailand [34]. Although causes of death were not available, we hypothesized that the increasing risk of death with DM may have been related to cardiovascular and renal complications as well as HIV infection itself.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that the risk of death in patients diagnosed DM tended to be higher after 4 years of follow-up, a finding similar to that reported by a previous study in Thailand [34]. Although causes of death were not available, we hypothesized that the increasing risk of death with DM may have been related to cardiovascular and renal complications as well as HIV infection itself.…”
Section: Discussionsupporting
confidence: 89%
“…This is a prospective study in an ongoing HIV Thai adult cohort (HIV-NAT 006 cohort, clinical trial number: NCT00411983). The details of this cohort have previously been described [ 16 18 ]. Participants were eligible for inclusion in this analysis if they achieved and maintained suppressed viremia at HIV-RNA < 50 copies/mL after starting cART.…”
Section: Methodsmentioning
confidence: 99%
“…A study in Taiwan suggested PLHIV to be as much as sixfold more likely to develop diabetes than the rest of the population, 69 and a recent Thai study of PLHIV showed diabetes developed at a younger age compared with the general population. 70 Increased rates of diabetes have also been reported in PLHIV in South Africa, 71 Tanzania 72 and Ethiopia. 71 Older ART drugs such as stavudine and zidovudine are known to increase the risk of metabolic syndrome and diabetes, and are used less now, so future studies may not confirm this relationship.…”
Section: Diabetes and Specific Infectionsmentioning
confidence: 98%